Micro, Small, and Medium Enterprises (MSMEs) Rebranding - Sholihah, Dienni Ruhjatini; Fadlillah, Alnisa Min; Mira Rahmi (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
Micro, Small, and Medium Enterprises (MSMEs) have great potential to drive the country’s economy, especially in developing countries like Indonesia. However, many views often reveal that MSMEs have low competitiveness. So, they are not considered a sustainable business and are not managed professionally, both in finance, marketing, and human resources. Therefore, currently, MSMEs are labeled as difficult to develop. This community service aims to change the paradigm of MSMEs through small steps to rebrand our MSME Partners. This activity is performed by providing assistance to the MSME participants that are related to 3 essential aspects: finance, marketing, and human resources. The assistance method in this program is carried out in some steps. The first step is carrying out observation since the location survey was carried out. Then, the implementation is carried out in these methods: lectures of theoretical presentations, assignments, practice trials, and finally, the designing of the rebranding model. With this program, the partners are expected to be able to improve and become MSMEs that are more competitive. They must have a positive image, so they can viewed as a professional business unit and generate significant profits.